Multiple Mellin Convolution and I-function Transformation involving r variables - Khan, Arif M (International Journal of Applied Mathematical Research, 2012)
An expression is obtained for an I-function of r variables, transform of the Multiple Mellin convolution of the two functions in terms of the Multiple Mellin convolution of I-function transforms of the function involving r variables, it generalize the result given earlier by Kumbhat and Khan [5].